Feasibility and outcomes of robot-assisted partial splenectomy for benign splenic lesions: a single-center experience - Chen, Xi; Jiang, Ting; Peng, Yonghai; Shi, Ruizi; Qin, Chuan; Luo, Hua; Zeng, Xintao; Yang, Pei; Wang, Jianjun (Frontiers in Surgery, 2026)
BackgroundTo evaluate the feasibility, safety, and short-term clinical outcomes of robot-assisted partial splenectomy (RAPS) in the treatment of benign splenic lesions (BSLs).MethodsA retrospective analysis was conducted on nine patients with BSLs who underwent RAPS in the Department of Hepatobiliary, Pancreatic, and Splenic Surgery at Mianyang Central Hospital between January 2024 and September 2025. Clinical data, including demographic characteristics, lesion features, intraoperative parameters, postoperative recovery, and complications, were collected. All patients underwent preoperative contrast-enhanced abdominal computed tomography, magnetic resonance imaging, and three-dimensional (3D) reconstruction to delineate the anatomical relationship between the lesion and splenic vasculature. All procedures were performed by the same surgical team.ResultsAll nine procedures were successfully completed without conversion to open surgery. The cohort comprised three men and six women, with a mean age of 49.0 ± 10.3 years. Lesions were located in the lower pole in seven cases and in the upper pole in two, with a mean diameter of 4.34 ± 0.8 cm. The mean operative time was 179.4 ± 15.5 min, the mean intraoperative blood loss was 71.1 ± 19.6 mL, and the mean postoperative hospital stay was 6.4 ± 0.9 days. No cases of splenic infarction, pancreatic fistula, hemorrhage, or severe infection were observed. Pathological diagnoses included splenic hemangioma (n = 3), non-parasitic splenic cyst (n = 5), and splenic lymphangioma (n = 1). During follow-up, no recurrence, new lesions, or splenic dysfunction were detected, and hematologic parameters remained within normal ranges.ConclusionRAPS is a safe, feasible, and minimally invasive spleen-preserving procedure. Preoperative 3D reconstruction facilitates precise surgical planning, and when combined with the high-precision maneuverability of robotic technology, enables complete lesion removal while preserving functional splenic tissue. This approach aligns with the principles of modern precision and minimally invasive surgery.